Natural product-derived phytochemicals as potential agents against coronaviruses: A review - Mani, Janice S.; Johnson, Joel B.; Steel, Jason C.; Broszczak, Daniel A.; Neilsen, Paul M.; Walsh, Kerry B.; Naiker, Mani (Virus research, 2020)
[Display omitted] •Naturally derived compounds provide a potential wealth of antiviral agents.•We reviewed the literature on phytochemicals against different human and animal coronaviruses.•Compounds showing the greatest potential for drug development are highlighted.•All promising compounds contain a conjugated ring structure.•Most are polyphenols and/or contain a substituted fused ring. Coronaviruses are responsible for a growing economic, social and mortality burden, as the causative agent of diseases such as severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS), avian infectious bronchitis virus (IBV) and COVID-19. However, there is a lack of effective antiviral agents for many coronavirus strains. Naturally existing compounds provide a wealth of chemical diversity, including antiviral activity, and thus may have utility as therapeutic agents against coronaviral infections. The PubMed database was searched for papers including the keywords coronavirus, SARS or MERS, as well as traditional medicine, herbal, remedy or plants, with 55 primary research articles identified. The overwhelming majority of publications focussed on polar compounds. Compounds that show promise for the inhibition of coronavirus in humans include scutellarein, silvestrol, tryptanthrin, saikosaponin B2, quercetin, myricetin, caffeic acid, psoralidin, isobavachalcone, and lectins such as griffithsin. Other compounds such as lycorine may be suitable if a therapeutic level of antiviral activity can be achieved without exceeding toxic plasma concentrations. It was noted that the most promising small molecules identified as coronavirus inhibitors contained a conjugated fused ring structure with the majority being classified as being polyphenols.